Production of cured, voided meat sausage with apple pomade added (Malus domestica) and its impact in nutritional and sensorial values - Loyola, Nelson; Acuña, Carlos; Arriola, Mariela (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2018)
The research was to compare 4 treatments with different percentages of vegetable fiber added, replacing animal fat, determining objectives, to use apple pomade as source of fiber in replace to meat sausage pork fat, assessment of nutritional recovery as fiber, fats, sugars and phenols; sensory attributes acceptability evaluate the presence of coliform bacteria, the sausage of pork including pomade apple (Malus domestica). The treatments were evaluated according to the goals set during the days 2, 15 and 30, to be processed, the results of nutritional analyzes showed differences in treatments with higher content of pomace, increasing the amount of fiber and mainly by decreasing the content fat. Regarding perceived by trained panelists thirteen observed differences in evaluating sensory attributes such as texture and acceptability of processed sausages when as much pomade apple was used. The results of microbiological analyzes met the requirements of the sanitary regulation of food Chile. The addition until 3% of apple pomade exhibited a higher score on the acceptability of the product.